Salivary Interleukins as Non-Invasive Biomarkers for Psoriasis: Advances and Challenges in Diagnosis and Monitoring - Anna Sora; Tony Hangan; Sergiu Ioachim Chirila; Leonard Gurgas; Mihaela Botnarciuc; Lavinia Carmen Daba; Ana Maria Cretu; Ionut Burlacu; Mihaela Zamfirescu; Adina Petcu; Adrian Cosmin Rosca; Ramona Mihaela Stoicescu; et al. (Medicina)
Background and Objectives: Psoriasis is a chronic immune-mediated inflammatory disease requiring reliable diagnostic and monitoring tools. Salivary interleukins have emerged as promising non-invasive biomarkers, reflecting systemic inflammation and offering practical advantages such as ease of collection and improved patient compliance. Materials and Methods: This review synthesizes the current evidence on key salivary cytokines—IL-1β, IL-6, TNF-α, and IL-17—in relation to psoriasis pathogenesis, diagnosis, and treatment monitoring. It also compares saliva to blood-based diagnostics, emphasizing benefits like cost-effectiveness and suitability for repeated sampling. Methodological challenges, including heterogeneity in collection protocols and limited longitudinal data, are critically examined. Results: Advances in biologic therapies have deepened the understanding of psoriasis immunopathogenesis, highlighting interleukins as central biomarkers. Recent findings identify IL-37 and IL-38 as novel regulatory cytokines with anti-inflammatory roles. While elevated serum TNF-α levels in psoriatic patients are well documented, some inconsistencies persist. Notably, saliva has proven to be a viable alternative diagnostic fluid, supporting large-scale screening and routine clinical monitoring. Conclusions: Salivary interleukins—particularly IL-1β, IL-6, TNF-α, and IL-17—represent valuable, non-invasive biomarkers for early detection, disease severity assessment, and therapeutic response monitoring in psoriasis. Standardizing saliva-based methods and conducting large-scale studies are essential next steps to support their integration into personalized clinical practice.